Emerging trends in the pretreatment of microalgal biomass and recovery of value-added products: A review - Pradhan N.; Kumar S.; Selvasembian R.; Rawat S.; Gangwar A.; Senthamizh R.; Yuen Y.K.; Luo L.; Ayothiraman S.; Saratale G.D.; Mal J. (My University, 2025)
Microalgae are a promising source of raw material (i.e., proteins, carbohydrates, lipids, pigments, and micronutrients) for various value-added products and act as a carbon sink for atmospheric CO2. The rigidity of the microalgal cell wall makes it difficult to extract different cellular components for its applications, including biofuel production, food and feed supplements, and pharmaceuticals. To improve the recovery of products from microalgae, pretreatment strategies such as biological, physical, chemical, and combined methods have been explored to improve whole-cell disruption and product recovery efficiency. However, the diversity and uniqueness of the microalgal cell wall make the pretreatment process more species-specific and limit its large-scale application. Therefore, advancing the currently available technologies is required from an economic, technological, and environmental perspective. Thus, this paper provides a state-of-art review of the current trends, challenges, and prospects of sustainable microalgal pretreatment technologies from a microalgae-based biorefinery concept. © 2022 Elsevier Ltd